Contesting heritage in the continuity of African traditional dances: an account of the jerusarema/mbende traditional dance of Zimbabwe - Mapira, Nesta Nyaradzo (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2016)
In African societies traditional dances are a form of cultural expression of emotional life occupying a prominent socio-cultural status. Due to colonisation, westernisation and Christianity many African traditional dances have changed in terms of the aesthetics. One of several traditional dances in Zimbabwe that has undergone continual socio-cultural and aesthetic change is Jerusarema from the Murehwa and Uzumba Maramba Pfungwe districts of Mashonaland Eastern province. In 2008, jerusarema dance, a widely recognised traditional and cultural expression in Zimbabwe, was included in the list of the United Nations Educational Scientific and Cultural Organisation’s (UNESCO’s) masterpieces of oral and intangible heritage of humanity. The listing made jerusarema one of the few African traditional dances accorded this recognition. Because of this recognition, jerusarema dance has been endorsed and used in multiple contexts by some performance ensembles such as Swerengoma, Ngomadzepasi and Dombodzvuku as promoted by prominent dance festivals. These ensembles assert their different agendas through music, props, instruments and western dancing styles often to the detriment of the perceived originality and authenticity of the dance. Drawing upon documentary video evidence from the National Arts Council of Zimbabwe and workshop notes, this paper examines issues of continuity and change in performance contexts, choreographies and principle performativity aesthetics. Videos recorded in 2015, showing Ngoma Dzepasi, Swerengoma and Dombodzvuku ensembles performing the dance, will be used to critique issues guided by jerusarema dance workshop notes taken whilst teaching music at Vumba Primary school 2014. I argue that UNESCO’s recognition of jerusarema dance as an intangible cultural heritage has, on the one hand, partially revived interest among Zimbabweans in jerusarema dance and, on the other hand, potentially compromised aesthetic principles and musical elements of jerusarema dance.